THE STUDY OF TRADITION AND MODERNITY IN THE NOVEL GADIS KRETEK BY RATIH KUMALA - Nia Kurniati; Dzela Kartika Ayuningtyas (ENGLISH JOURNAL, 2024)
The novel "Gadis Kretek" by Ratih Kumala explored the rich tapestry of Indonesian culture, blended traditional values with the nuances of modernity. This study aimed to examine the interplay between tradition and modernity in "Gadis Kretek." It sought to understand how Ratih Kumala portrayed the tension between these two forces and how this portrayal reflected the broader socio-cultural context of Indonesia. The research employed a qualitative approach, utilizing literary analysis to dissect the novel’s themes, characters, and narrative structure. Key elements such as cultural representation, character development, and the historical backdrop of the kretek industry are analyzed to uncover the underlying messages about tradition and modernity. The analysis revealed that "Gadis Kretek" juxtaposes traditional Javanese cultural elements with the encroachment of modern values and economic practices. Characters in the novel navigated these conflicting forces, showcasing the resilience of tradition amidst inevitable change. The kretek industry served as a symbol of this duality, representing both heritage and progress. Ratih Kumala’s "Gadis Kretek" effectively captured the dynamic interplay between tradition and modernity in Indonesian society. The novel highlights the challenges and adaptations faced by individuals and communities in preserving cultural identity while embracing modern advancements. This study underscored the importance of literary works in reflecting and shaping societal values and transitions.